Upaya Meningkatkan Minat Belajar Siswa Dengan Menggunakan Metode Team Teaching Dalam Pembelajaran PAI Di SMP Negeri 7 Kebumen - Fadilah, Farida Nurul; Markhumah, Ngatiqotul; Fatimah, Siti; Subarkah, Imam (IAINU Kebumen, 2022)
The active attitude of students is the main capital for successful PAI learning. As many as 75% of students at SMPN 7 Kebumen are not enthusiastic and tend to be inactive. This study aims to determine the increase in student interest in learning by using the team teaching method in PAI learning. The research method used is classroom action research which consists of two cycles with the stages of planning, taking action, observing, and reflecting. The research subjects were students of class VII H of SMPN 7 Kebumen for the academic year 2021/2022, totaling 30 students. The goal to be achieved in this research is to increase students' interest in learning PAI with the team teaching method with the hope that students can be actively involved in learning activities. From the data obtained in the pre-cycle, the percentage of student activity was 24.5%, in the first cycle it increased to 62.08% and there was an increase in student activity to 87.09% in the second cycle. In other words, the implementation of learning actions through the team teaching method can increase student interest in learning PAI. Abstrak Sikapaktif yang dimiliki siswa merupakan modal utama keberhasilan belajar PAI. Sebanyak 75 % siswa di SMP Negeri 7 Kebumen tidak bergairah dan cenderung tidak aktif. Penelitian ini bertujuan untuk mengetahui peningkatan minat belajar siswa dengan menggunakan metode team teaching dalam pembelajaran PAI. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) yang terdiri dari dua siklus dengan tahapan kegiatan perencanaan, melakukan tindakan, observasi serta refleksi. Subyek penelitian adalah siswa kelas VII H SMP Negeri 7 Kebumen Tahun pelajaran 2021/2022 yang berjumlah 30 siswa. Adapun tujuan yang ingin dicapai dalam penelitian ini adalah meningkatkan minat belajar siswa dalam pembelajaran PAI dengan metode team teaching dengan harapan siswa dapat melibatkan diri secara aktif dalam kegiatan pembelajaran. Dari data yang diperoleh pada pra siklus presentase aktivitas siswa sebesar 24,5 %, pada siklus I meningkat menjadi 62,08 % dan terjadi peningkatan aktivitas siswa menjadi 87,09 % di siklus II. Dengan kata lain, implementasi tindakan pembelajaran melalui metode team teaching dapat meningkatkan minat belajar siswa dalam pembelajaran PAI.